Diseño e implementación de una arquitectura y metodología aplicadas al monitoreo remoto de variables meteorológicas - Calderón Córdova, Carlos Alberto (2017)
The measurement of weather variables in the Andes Mountains of Ecuador is of great importance for environmental, hydrological and ecological research. Such investigations reveal indicators that contribute to innovative management of Territorie, which it is characterized as a biodiverse natural heritage. Due to heterogeneity of the distribution of rainfall and other weather variables in in that region suggest the need to use radar systems LAWR (Local Area Weather Radar), to mapping of variables with high temporal and spatial resolution. However, the outputs of these radar systems are required to calibrate in real-time with ground nodes measurements. Therefore, the radar system LAWR, available in the province of Loja-Ecuador intended for research between the University (UTPL) and the autonomous governments (GADs), needs to be complemented with real-time monitoring of variables acquired by the reference weather stations located in the study area. Based on the above, the objective of this work is to design, implement and evaluate a remote real-time monitoring system of weather variables acquired by measuring ground stations based on Davis Vantage Pro. The implemented system is based on GPRS and provides reliable (max. error 1.5%) and timely (every 5 min.) information to enable to researchers intelligent management of territories. Keywords: remote monitoring; weather stations; GPRS networks; data acquisition; Davis Vantage Pro.